Security-Experience Alignment in Smart Tourism: Empirical Validation of the SEAM Framework - Tsiakalos, Apostolos (Turizam, 2026)
Purpose: This study proposes and empirically validates a novel conceptual framework — the Security-Experience Alignment Model (SEAM) — which investigates how objective cybersecurity conditions mediate the relationship between perceived digital trust and tourist satisfaction in smart tourism ecosystems.Design/methodology/approach: A sequential mixed-method research design was adopted. First, quantitative survey data from 210 thematic travelers was collected to assess satisfaction drivers, hygiene perceptions, and cybersecurity awareness. Second, a technical cybersecurity audit was conducted on representative smart tourism infrastructures, including wireless access points and mobile applications, utilizing penetration testing tools. The dataset was analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) to identify mediation effects and direct relationships.Findings: Results reveal a statistically significant decoupling between perceived digital trust and actual security posture of tourism infrastructures. While personalization and smart services enhance satisfaction, infrastructural vulnerabilities reduce underlying trust without immediate impact on satisfaction scores. The SEAM framework identifies cybersecurity resilience as a latent variable that indirectly affects long-term tourist loyalty intentions. Originality/value: The study contributes to the evolving discourse on smart tourism by theoretically integrating cybersecurity resilience into models of tourist satisfaction and trust. It advances prior literature by demonstrating the mediating role of infrastructural security in shaping visitor experiences and provides actionable insights for designing secure-by-default smart tourism ecosystems.